2021
DOI: 10.1101/2021.02.08.21250309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospitalizations for emergency-sensitive conditions in Germany during the Covid-19 pandemic Insights from the German-wide Helios hospital network

Abstract: Background: While there are numerous reports that describe emergency care during the early Covid-19 pandemic, there is scarcity of data for later stages. This study analyzes hospitalization rates for 37 emergency-sensitive conditions in the largest German-wide hospital network during different pandemic phases. Methods: Using claims data of 80 hospitals, consecutive cases between January 1 and November 17, 2020 were analyzed and compared to a corresponding period in 2019. Incidence-rate ratios (IRR) comparing t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Similar studies have also demonstrated increase in the incidence of aortic dissection, along with other cardiovascular manifestations such as myocardial infarction and aortic aneurysms in the first wave of Covid-19. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have also demonstrated increase in the incidence of aortic dissection, along with other cardiovascular manifestations such as myocardial infarction and aortic aneurysms in the first wave of Covid-19. 39 …”
Section: Discussionmentioning
confidence: 99%